Local People’s Perception of Ecotourism: the Case of Salda Lake - Yayla, Özgür; Çinbilgel, İlker and Dağdelen, Özlem (Anais Brasileiros de Estudos Turísticos, 2021)
The present research was carried out in the sample of Salda Lake in Turkey in order to determine the perception of local residents about cultural, economic and environmental effects of ecotourism and to identify the effect of these variables on their support for tourism development in the region. In the research, it was concluded that cultural, economic and environmental effects of ecotourism act as an antecedent of the support by local people residing around Salda Lake on tourism development in the region. In addition, the local people’s length of residence in the region creates a moderating effect in the relationship between cultural, economic and environmental effects of tourism and the residents’ support for tourism development. The research findings provide suggestions to tourism planners, destination management organizations (DMO) and academicians studying in the context of tourism literature.